An effective hybrid strategy for converting rice straw to furoic acid by tandem catalysis via Sn-sepiolite combined with recombinant E. coli whole cells harboring horse liver alcohol dehydrogenase. Issue 21 (4th October 2019) - Peng, Bo; Ma, Cui-Luan; Zhang, Peng-Qi; Wu, Chang-Qing; Wang, Zi-Wei; Li, Ai-Tao; He, Yu-Cai; Yang, Bin
Abstract : The upgrading of biomass-derived furfural into high-value bio-based chemicals has attracted interest. Abstract : The upgrading of biomass-derived furfural into high-value bio-based chemicals has attracted interest. In this case, the conversion of rice straw into furfural was firstly performed using tin-loaded sepiolite (Sn-sepiolite) as a catalyst. Acidified solid acid Sn-sepiolite (3.0 wt%) converted alkali-pretreated dewaxed rice straw into furfural at 42.2% yield at 170 °C for 20 min. Moreover, biomass-derived furfural could be completely converted into furoic acid with recombinant immobilized E. coli TS whole-cells within 96 h at pH 7.0 and 30 °C, respectively. Finally, efficient recycling and reuse of the Sn-sepiolite catalyst and immobilized TS whole-cell biocatalyst were developed for the synthesis of furoic acid from rice straw in the one-pot reaction system. In summary, an effective one-pot chemo-enzymatic synthesis of furoic acid from renewable biomass was successfully developed using ambient conditions.